Ø§Ù„ÙØµÙ„ Ø§Ù„Ø§Ø¹Ø¯Ø§Ø¯ÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø§Ø®ØªØ¨Ø§Ø± ÙƒÙØ§Ø¡Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ø£Ø¬Ø§Ù†Ø¨ (TOAFL) (Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØØ§Ù„Ø© ÙÙŠ Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¥Ø¨Ø±Ø§Ù‡ÙŠÙ…ÙŠ Ø¨Ø§Ù†ÙŠÙˆÙˆØ§Ù†Ù‚ÙŠ Ø¬ÙˆØ§ Ø´Ø±Ù‚ÙŠØ©) - Hidayah, Fathi (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2015)
TOEFL (Test of Arabic as Foreign Language) is a test to measure the ability to speak Arabic. This test is used as a prerequisite in thesis writing at several universities. Language skills tested in TOAFL include Maharah istima ?and Maharah qira?ah. Both Maharah includes elements mufradat, qawaid wa tarakib an nahwiyyah, fahm nash al masmu ?, and fahm nash al maqru?. To facilitate the students attend and solve problems such TOAFL, UPT Language IAI Ibrahimy Banyuwangi held TOAFL Preparation Class (Fashl al I?dady) that the material in the form of the materials tested in the TOAFL.